1977
DOI: 10.1126/science.196.4289.489
|View full text |Cite
|
Sign up to set email alerts
|

Radioisotope Dating with a Cyclotron

Abstract: By considering radioisotope dating as a problem in trace element detection, and by using the cyclotron as a high-energy mass spectrometer for this purpose, we have shown that one can greatly increase the maximum age that can be determined while simultaneously reducing the size of the sample required. The cyclotron can be used to detect atoms or simple molecules that are present at the 10(-16) level or greater. For (14)C dating one should be able to go back 40,000 to 100,000 years with 1- to 100-mg carbon sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
119
0
22

Year Published

1980
1980
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 318 publications
(142 citation statements)
references
References 21 publications
1
119
0
22
Order By: Relevance
“…The ion source memory effect would have had to be solved, for example. The proposal by Muller (1977) to actually use a cyclotron for 14 C dating was not made until 1977 after extensive development work on accelerators, ion sources, and sensitive detection methods. The maturity of nuclear physics was then also generating imaginative ways to look for free quarks Stephenson et al 1977), super heavy elements (Schwartzschild et al 1977), and other trace entities suggested by the developments in the physics of the nucleon and nucleus.…”
Section: Origins Of 14 C Ion Counting By Amsmentioning
confidence: 99%
“…The ion source memory effect would have had to be solved, for example. The proposal by Muller (1977) to actually use a cyclotron for 14 C dating was not made until 1977 after extensive development work on accelerators, ion sources, and sensitive detection methods. The maturity of nuclear physics was then also generating imaginative ways to look for free quarks Stephenson et al 1977), super heavy elements (Schwartzschild et al 1977), and other trace entities suggested by the developments in the physics of the nucleon and nucleus.…”
Section: Origins Of 14 C Ion Counting By Amsmentioning
confidence: 99%
“…As a result, our program to date has been directed toward the more abundant trace gases and atmospheric particles; measurements have been made practicable for samples containing as little as 5mg carbon through the development of a specially-designed mini-radiocarbon counting system (Currie and others, 1978). Most recently, as noted in the final section of this paper, the development of the direct atom-counting method of Accelerator Mass Spectrometry (Muller, 1977;Gove, 1978) has enormously enhanced our potential to derive environmental information from radiocarbon measurements, as samples containing only a few tens of micrograms of carbon may now be analyzed (Currie and others, ms figure 1. In all cases, radiocarbon measurements were supplemented by serial or parallel chemical selectivity ("supporting data" -last column), and sample sizes (with one exception) consisted of about 10mg carbon.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…wood * Radiocarbon errors represent one (Poisson) standard deviation; other indicators, which are subject to significant assumption-related uncertainties, are given for qualitative comparison (Cooper, Currie, and Klouda, in press (1979) and Trefil (1978), on environmental significance and impacts, in Cooper, Currie, and Klouda (in press) and Butcher (1978), Of critical importance to our program to resolve individual sources of carbonaceous species, and to increase our knowledge of spatial and temporal variations, is the ability to determine radiocarbon in extremely small samples. While small proportional counters will continue to provide much of the information we need, reliably and inexpensively, a major promise for the future is direct 14C atom counting by means of Accelerator Mass Spectrometry (AMS) (cove, 1978;Muller, 1977). The ability to determine natural radiocarbon in microgram samples will permit us to assay gaseous halocarbons, aromatic hydrocarbons, and trapped or adsorbed polycyclic and oxygenated organic compounds that have allegedly arisen from anthropogenic or natural sources.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…The 99 Mo/ 99m Tc parent/daughter pair is one example of a generator system. But many other important generator systems include 68 Ge/ 68 Ga, 82 Sr/ 82 Rb, 90 Sr/ 90 Y, and 188 W/ 188 Re. For example, the 270.8 day 68 Ge isotope is the parent to the 1.13 hour daughter, 68 Ga, and 68 Ga is routinely used to label certain types of tumors for PET scanning.…”
Section: Production Of Radioisotopesmentioning
confidence: 99%
“…But many other important generator systems include 68 Ge/ 68 Ga, 82 Sr/ 82 Rb, 90 Sr/ 90 Y, and 188 W/ 188 Re. For example, the 270.8 day 68 Ge isotope is the parent to the 1.13 hour daughter, 68 Ga, and 68 Ga is routinely used to label certain types of tumors for PET scanning. In general, if the generator system involves a parent with decay constant λ p and a daughter with decay constant λ d , with λd>>λp, the system will reach an equilibrium state such that the ratio of the parent to daughter atoms is approximately constant,…”
Section: Production Of Radioisotopesmentioning
confidence: 99%